ANALISIS PEMIKRAN MUHAMMAD MANSHUR AL-BATAWI TERHADAP HISAB RUKYAT DALAM KITAB SULLAM NAYYIRAIN - Kaharuddin, Rahman; Wakia, Nurul (HISABUNA: Jurnal Ilmu Falak, 2025)
Abstract “This article discusses Manshur al Batawi's analysis of Hisab Rukyat in the Book of Sullam Nayyirain. Research on hisab rukyat the author refers to the thought of hisab rukyat Muhammad Manshur al-Batawi in the Sullamun Nayyirain Book, with the research approach used being the astronomical, syar'i approach, and the character approach in this case, Muhammad Manshur al-Batawi from the results of this research found that Muhammad Masnhur al-Batawi's reckoning thoughts are basically the thoughts of a network of scholars with Arab scholars including Syek Abdurrahman al-Misri, Mansur's teacher who received his first education directly from his parents who were scholars. Mas Manshur al-Batawi's ruyat reckoning thought uses Ptolemy's theory which has a geocentric principle, which according to scientific history has been superimposed by the heliocentric principle. So it is natural that the calculation results include the true reckoning of taqribi, to calculate the time of ijtima', solar eclipse and lunar eclipse. To calculate the beginning of the month of Kamariyah according to this book, start by calculating when ijtima' occurs. The technique for calculating the height of the new moon at sunset is by finding the difference between the sunset time and the ijtima' time that occurs before Ghurub, so that night the new moon has entered. The implication of this research is that every student of science should seek as much knowledge as possible, as was done by Muhammad Manshur al-Batawi who did not look at age in seeking knowledge, especially for those interested in astronomy, so that the knowledge gained can be a source of knowledge for us and those who are also interested in learning. learn from us. Like now, the work of Muhammad Manshur al-Batawi is a charity for him because many of his works are used as writing references.